2012
DOI: 10.1007/s10800-012-0379-3
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalysis of urinary l-dopa using tyrosinase immobilized on gold nanoelectrode ensembles

Abstract: The performance of an amperometric biosensor constructed by associating tyrosinase (Tyr) enzyme with the advantages of a 3D gold nanoelectrode ensemble (GNEE) is evaluated in a flowinjection analysis (FIA) system for the analysis of Levodopa (Ldopa). GNEEs were fabricated by electroless deposition of the metal within the pores of polycarbonate track-etched membranes. A simple solvent etching procedure based on the solubility of polycarbonate membranes is adopted for the fabrication of the 3D GNEE. Afterwards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…A schematic representation of how the biosensor is prepared is shown in Figure A, which comprises of 4 steps involving the electroless gold deposition in polycarbonate membranes, followed by partial etching exposing gold nanoarrays. Figure B shows an SEM image of the 3D GNEE which shows that the gold nanowires have an average diameter of 50 nm and a length of 180 (±20) nm which also shows the absence of voids on surface, which suggest that this method produces 3D GNEEs with protruding gold wires . The 3D GNEE was explored toward the sensing of L-DOPA using a flow-injection analysis system, as shown in Figure C where a linear current response for L-DOPA between 10 nM and 10 mM was achieved.…”
Section: Electroanalytical Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…A schematic representation of how the biosensor is prepared is shown in Figure A, which comprises of 4 steps involving the electroless gold deposition in polycarbonate membranes, followed by partial etching exposing gold nanoarrays. Figure B shows an SEM image of the 3D GNEE which shows that the gold nanowires have an average diameter of 50 nm and a length of 180 (±20) nm which also shows the absence of voids on surface, which suggest that this method produces 3D GNEEs with protruding gold wires . The 3D GNEE was explored toward the sensing of L-DOPA using a flow-injection analysis system, as shown in Figure C where a linear current response for L-DOPA between 10 nM and 10 mM was achieved.…”
Section: Electroanalytical Approachesmentioning
confidence: 99%
“…Pinho et al reported the use of a 3D gold nanoelectrode ensemble (GNEE) in a flow-injection analysis system for the sensing of L-DOPA. A schematic representation of how the biosensor is prepared is shown in Figure A, which comprises of 4 steps involving the electroless gold deposition in polycarbonate membranes, followed by partial etching exposing gold nanoarrays.…”
Section: Electroanalytical Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon nanotube sensors improve the sensitivity of detection by increasing the available surface area and potentially by altering the activity and electron transport of the targeted biomolecule by bringing the electrode surface closer to the enzyme's active site (105,106). The use of nanoelectrodes confers unique advantages on amperometric biosensors, as shown recently by the detection of glucose (107,108) and L-dopa (109). The increased surface area and small dimensions of nanoelectrodes increase the sensors' sensitivity and enhance mass transport through the use of hemispherical diffusion fields (110).…”
Section: Research Examplesmentioning
confidence: 99%